The main benefits associated with health and safety management systems certification in Portuguese small and medium enterprises post quality management system certification - Santos, Gilberto (2013)
The purpose of this study is to characterize how Portuguese Small and Medium Enterprises (SMEs) view the Occupational Health and Safety Management Systems (OHSMSs) certification process, after receiving the Quality Management System (QMS) certification. References were based on the ISO 9001 standard for a QMS and OHSAS 18001 for OHSMS. The method used to evaluate the implemented systems, was by form of questionnaire. Those questioned had to have a certified quality management system, an implemented OHSMS and be a SME. The questionnaire was sent to 300 SMEs; 46 responses were received and validated. Of them, only 12 SMEs had the OHSMS certificate according to OHSAS 18001. Within those 12 companies that participated: 7 SMEs are from the industrial sector; 3 belong to the electricity/telecommunications sector and 2 SMEs are from the trade/services activity sector. The size of the sample was small, but corresponds to Portuguese reality. Moreover, 34 SMEs did not have the OHSMS certificate. The questionnaire requested the main reasons for SMEs to opt for non-certification and it was related with high costs, while the main reasons to certificate were, among others, needed to eliminate or minimize risks to workers. The main benefits that Portuguese SMEs have gained from the referred certifications have been, improved working conditions, ensuring compliance with legislation and better internal communication about risks and hazards. Also presented are the main difficulties in achieving an OHSMS certification including high certification costs, difficulties motivating personnel, difficulties in changing the company’s culture and increased bureaucracy.